Short Assessment of Health Literacy for Portuguese-speaking Adults - Daniel Apolinario; Rafaela de Castro Oliveira Pereira Braga; Regina Miksian Magaldi; Alexandre Leopold Busse; Flavia Campora; Sonia Brucki; Shoou-Yih Daniel Lee (Universidade de São Paulo, 2012)
OBJECTIVE: To develop and validate a short health literacy assessment tool for Portuguese-speaking adults. METHODS: The Short Assessment of Health Literacy for Portuguese-speaking Adults is an assessment tool which consists of 50 items that assess an individual's ability to correctly pronounce and understand common medical terms. We evaluated the instrument's psychometric properties in a convenience sample of 226 Brazilian older adults. Construct validity was assessed by correlating the tool scores with years of schooling, self-reported literacy, and global cognitive functioning. Discrimination validity was assessed by testing the tool's accuracy in detecting inadequate health literacy, defined as failure to fully understand standard medical prescriptions. RESULTS: Moderate to high correlations were found in the assessment of construct validity (Spearman's coefficients ranging from 0.63 to 0.76). The instrument showed adequate internal consistency (Cronbach's alpha=0.93) and adequate test-retest reliability (intraclass correlation coefficient=0.95). The area under the receiver operating characteristic curve for detection of inadequate health literacy was 0.82. A version consisting of 18 items was tested and showed similar psychometric properties. CONCLUSIONS: The instrument developed showed good validity and reliability in a sample of Brazilian older adults. It can be used in research and clinical settings for screening inadequate health literacy.